FREQUENCY AND CLINICAL PRESENTATION OF CEREBELLOPONTINE ANGLE TUMORS: AN EXPERIENCE IN DEPARTMENT OF NEUROSURGERY LADY READING HOSPITAL PESHAWAR - Zahid, Seema; Ullah, Wefaq; Khan, Zahid; Ali, Mumtaz (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the frequency and clinical presentation of cerebellopontine (CP) angle tumors in Department of Neurosurgery, Lady Reading Hospital Peshawar. Methodology: Descriptive cross sectional study was conducted from July 2014 to June 2015(one year) in Department of Neurosurgery, Lady Reading Hospital Peshawar. All patients having primary CP Angle tumors were included. patients having recurrent CPA tumor, vascular pathology and CP angle tumors managed conservatively were excluded. Data of the target population was then collected on a designed profarma from the hospital charts, radiology and histopathology reports. Patients were analyzed on the basis of age and gender. Data was entered into statistical program SPSS 16 and was expressed in percentages. Data was presented in different tables. Results: 14 patients (53.85%) out of 26 were female and 12 patients (46.15%) were male with male to female 1:1.7. Eight cases (30.77%) were below 40 years and 18 cases (69.23%) were above 40 years with mean age of 42 years. Eighteen (18) cases (69.23%) were acoustic neuroma and 4 cases (15.38%) were meningioma, 3 cases (11.54%) were epidermoid and 1 case (3.85%) was arachnoid cyst. The most common presenting symptom was hearing loss which accounts for 69.23%. It is followed by headache (53.85%), tinnitus and disequilibrium (38.46%) each, papilledema (30.77%), vomiting, visual impairment and facial weakness (23.08%) each, diplopia and nystagmus (15.38%) each and focal deficit (7.69%). Conclusion: The most common cerebellopontine angle tumor is acoustic neuroma which is followed by meningioma, epidermoid and arachnoid cyst. The most common presenting symptom is hearing loss which is followed by headache, tinnitus and disequilibrium.